Faktor Risiko Gizi Lebih Pada Dewasa Muda : Konsumsi Minuman Manis Dan Perilaku Sedentari - Aryanti Setyaningsih (Poltekkes Kemenkes Semarang, 2025)
Background: The incidence of overnutrition in adults over 18 years old, based on the 2023 Indonesian Health Survey, is 14.4% overweight and 23.4% obese. Overnutrition in Indonesia is estimated to continue to increase. Factors that influence overnutrition are unhealthy eating habits and low physical activity. This study aims to analyze the incidence of overnutrition and is caused by the consumption of sweet drinks and sedentary lifestyle on the incidence of overnutrition in the young adult age group in Ungaran. Method: The research was conducted from January to March 2024 in Ungaran with an observational design and cross-sectional approach. This research involved 104 respondents who were selected using proportional random sampling, with the inclusion criteria being between 18-25 years old and willing to be respondents. The exclusion criteria include individuals who are sick, have an infectious or chronic disease, or were hospitalized a week before data collection. Respondents' nutritional status data were obtained based on height and weight measurements, which were then categorized based on body mass index. Interviews were conducted to obtain data on the consumption of sweet drinks using the Semi-Quantitative Food Frequency Questionnaires (SQ-FFQ), while interviews regarding sedentary behavior were conducted using the Sedentary Behavior Questionnaire (SBQ). Bivariate analysis used Kendall Tau analysis (Î±=0.05). Results: A total of 60 respondents (57.7%) experienced overnutrition. There were 57 respondents (54.8%) who consumed sweet drinks in the high category, and 82 (78.8%) respondents had sedentary behavior in the high category. Consumption of sweet drinks and sedentary behavior are related to overnutrition in young adults in Ungaran. (p < 0.05). Conclusion: Consumption of sweet drinks and sedentary behavior are risk factors for overnutrition among young adults in Ungaran.Keywords: overnutrition; sweet drinks; sedentary behavior; young adult